2017
DOI: 10.1186/s13002-017-0187-2
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ perception of termites in agriculture production and their indigenous utilization in Northwest Benin

Abstract: BackgroundAlthough termites are considered as agricultural pests, they play an important role in maintaining the ecosystem. Therefore, it matters to investigate the farmers’ perception of the impacts of the termites on the agriculture and their indigenous utilization.MethodsA semi-structured questionnaire was used to interview 94 farmers through 10 villages of Atacora department, in the northwestern region of Benin, to obtain information for the development of successful strategies of termite management and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…It is important to note that termites exhibited a preference for different types of residues. The maize crop residues were definitely preferred over sunn hemp (Yêyinou Loko et al ., 2017), which again is in response to residue quality, C : N ratio and the composition of maize stalks compared with sunn hemp residues.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that termites exhibited a preference for different types of residues. The maize crop residues were definitely preferred over sunn hemp (Yêyinou Loko et al ., 2017), which again is in response to residue quality, C : N ratio and the composition of maize stalks compared with sunn hemp residues.…”
Section: Discussionmentioning
confidence: 99%
“…For example, farmers generally perceive termites as pests of several agricultural crops and apply various indigenous control practices (Yêyinou Loko et al ., 2017). However, these farmers also use some termite species as food and medicinal resources, highlighting the need for a more sophisticated approach to termite control in order to assure the conservation of non‐pest termite species (Yêyinou Loko et al ., 2017). While some farmers can identify several termite species on their farms using their indigenous names, many others lack this knowledge (Yêyinou Loko et al ., 2017).…”
Section: Integrative Evaluation Of Ecosystem Services and Disservicesmentioning
confidence: 99%
“…However, these farmers also use some termite species as food and medicinal resources, highlighting the need for a more sophisticated approach to termite control in order to assure the conservation of non‐pest termite species (Yêyinou Loko et al ., 2017). While some farmers can identify several termite species on their farms using their indigenous names, many others lack this knowledge (Yêyinou Loko et al ., 2017). Such indigenous taxonomic skills are vital for communication between researchers, extension agents, educators, and farmers for social insect management programmes (Orikiriza, Nyeko & Sekamatte, 2012).…”
Section: Integrative Evaluation Of Ecosystem Services and Disservicesmentioning
confidence: 99%
“…Macrotermes bellicosus (Smeathman, 1781), a species belonging to the Macrotermitidae is native to the Republic of Benin where it is considered a natural resource for nutritional, cultural and medicinal purposes. The main consumed castes are winged, soldier and occasionally queen termites for cultural and rituals events [3,4]. In a previous ethnomedicinal survey, it was found that M. bellicosus is mainly used to treat digestive disorders, mumps, snake bites, cough, diarrhea, dysentery and pulmonary infection in different districts of northern Benin [4].…”
Section: Introductionmentioning
confidence: 99%